Bacterial Contamination and Disinfection Status of Laryngoscopes Stored in Emergency Crash Carts - Jae Hyung Choi; Young Soon Cho; Jung Won Lee; Hee Bong Shin; In Kyung Lee (Korean Society for Preventive Medicine, 2017)
Objectives To identify bacterial contamination rates of laryngoscope blades and handles stored in emergency crash carts by hospital and area according to the frequency of intubation attempts. Methods One hundred forty-eight handles and 71 blades deemed ready for patient use from two tertiary hospitals were sampled with sterile swabs using a standardized rolling technique. Samples were considered negative (not contaminated) if no colonies were present on the blood agar plate after an 18-hour incubation period. Samples were stratified by hospital and according to the frequency of intubation attempts (10 attempts per year) using the χ2-test and Fisher exact test. Results One or more species of bacteria were isolated from 4 (5.6%) handle tops, 20 (28.2%) handles with knurled surfaces, and 27 (18.2%) blades. No significant differences were found in microbial contamination levels on the handle tops and blades between the two hospitals and two areas according to the frequency of intubation attempts. However, significant differences were found between the two hospitals and two areas in the level of microbial contamination on the handles with knurled surfaces (p<0.05). Conclusions Protocols and policies must be reviewed to standardize procedures to clean and disinfect laryngoscope blades and handles; handles should be re-designed to eliminate points of contact with the blade; and single-use, one-piece laryngoscopes should be introduced.